Dimensi Filosofis Al-Qur’an: Eksplorasi Metafisika, Epistemologi, dan Etika - Imamuddin Imamuddin (VIRTUOUS JOURNAL, 2024)
This study explores the philosophical dimensions embedded within the Qur’an, focusing on three central domains: metaphysics, epistemology, and ethics. While the Qur’an is primarily regarded as a revealed scripture, its discourse contains profound philosophical insights that have shaped the intellectual tradition of Islamic thought. Using a qualitative and analytical approach, this research examines key Qur’anic concepts related to the nature of reality (ontology), sources of knowledge, and moral frameworks. The findings demonstrate that the Qur’an presents a coherent philosophical worldview grounded in divine unity (tawḥīd), integrating metaphysical assertions with epistemological guidance and ethical imperatives. Furthermore, the study argues that Qur’anic philosophy is not abstract speculation but a lived and practical framework that bridges reason and revelation. This research contributes to contemporary discussions by highlighting the relevance of Qur’anic philosophy in addressing modern intellectual and ethical challenges.